VDC_100102370104.0X000001. Issue 2 (February 2018) - Rosemurgy, Alexander; Whitaker, Jacqueline; Luberice, Kenneth; Rodriguez, Christian; Downs, Darrell; Ross, Sharona
Surgical Site Infections (SSI) represent an onerous burden on our health-care system. This study was undertaken to determine the impact of a protocol aimed at reducing SSIs on the frequency and cost of SSIs after abdominal surgery. Beginning in 2013, 811 patients undergoing gastrointestinal operations were prospectively followed. In 2014, we initiated a protocol to reduce SSIs. SSIs were monitored before and after protocol implementation, and differences in SSI incidence and associated costs were determined. Before protocol initiation, standardized operative preparation cost was $40.85 to $126.94 per patient depending on the results of methicillin-resistant Staphylococcus aureus screen; after protocol initiation, the cost was $43.85 per patient, saving up to $83.09 per patient. With the protocol in place, SSI rate was reduced from 4.9 to 3.4 per cent (13 of 379) representing a potential prevention of eight infections that would have cost payers $166, 280 ($20, 785 per infection). Notably, the SSI rate after pancreatectomy was reduced by 63 per cent ( P = 0.04). With preparation and diligence, SSI rate can be meaningfully reduced and potential cost savings can be achieved. In particular, SSI rate reduction for major abdominal operations and especially pancreatic resections can be achieved. A protocol to reduce SSI is a "win-win" for all stakeholders and should be encouraged with thoughtful and active participation from all hospital disciplines.